Analysis of Interfaith Marriage Legality in Indonesia and South East Asia Countries - Kurniawan, Itok Dwi; Septiningsih, Ismawati; Nuryadi, Muhammad Hendri; Santos, Jose Gama (Universitas Lampung, 2024)
Interfaith marriage in Indonesia is still a problem in Indonesia which is supported by multiple interpretations of regulations. The author in this article will discuss the analysis of interfaith marriage in Indonesia after the issuance of SEMA Number 2 of 2023. This article was made with the aim of analyzing and comparing regulations in Indonesia with other countries. The results of the study show that after the issuance of SEMA, the practice of interfaith marriage still occurs in Indonesia, which is also supported by the lack of government firmness in establishing the applicable regulations.